Literature Review of Social Science Learning Methodology (IPS) - Febri Aris Susanto (Madrosatuna: Journal of Islamic Elementary School, 2017)
Social Sciences is a subject that studies and discusses social issues in society. The learning process of a subject will take place well and smoothly if the teacher in delivering the material has strategies and methods in delivering it to the students. The purpose of this article is to describe the social science learning methodology from literature review analysis. The method used is to use various literature review on the social science learning methodology. The social science is a field of study in the learning process is expected to provide students to be responsible in social life. Somesocial science learning methodologies are tailored to the conditions of students and facilities available so as to provide good learning outcomes with indicators of mastery and student learning achievement.